AMRAPĀLI AND THE SACRED REDEMPTION: TRANSFORMATION OF A COURTESAN IN GANDHĀRA BUDDHIST ART AND LITERATURE - Dr Qamar-un-Nisa; Dr Farhat Nasim (Journal of Religion and Society, 2025)
This article examines the artistic and spiritual legacy of Amrapāli, the celebrated courtesan of ancient Vaiśālī, through the lens of Gandhāra Buddhist art. By analyzing key sculptural reliefs, the study reveals how Gandhāran artists constructed a visual narrative of female spiritual agency, contrasting Amrapāli’s transformative journey with conventional depictions of women in early Indian art. The iconographic analysis demonstrates her dual representation both as a courtesan and a devout disciple encoded through symbolic attributes such as the water flask (kamaṇḍalu) and mango grove, which signify her transition from worldly indulgence to monastic devotion. The spatial composition of these reliefs, particularly her placement alongside male donors and monks, challenges traditional gender hierarchies, reflecting Buddhism’s radical egalitarian ethos. A comparative study with Queen Māyā highlights the distinct archetypes of female spirituality in Gandhāra art: while Māyā embodies sacred motherhood, Amrapāli represents self-determined enlightenment outside prescribed social roles. Her story, preserved in texts like the Dīgha Nikāya and Therīgāthā, finds visual reinforcement in Gandhāran reliefs, where progressive simplification of her adornment mirrors her spiritual evolution. The article also explores her lasting impact on South Asian visual culture, influencing later Buddhist art across Asia and inspiring modern reinterpretations that reclaim her as a proto-feminist figure. Ultimately, this study underscores the role of Gandhāra art in shaping public memory of religious women, presenting Amrapāli as a symbol of redemption, moral transformation, and gender inclusion. Her legacy endures as a testament to the power of art to immortalize marginalized voices and affirm the possibility of spiritual liberation beyond societal constraints. Keywords: Amrapāli, Gandhāra Art, Buddhist Women, Gender And Spirituality, Iconography, Female Agency, Sacred Transformation, Ancient India, Visual Narrative, Redemption